The Influence of Leadership Style, Organizational Culture, and Compensation on Employee Performance Through Motivation as an Intervening Variable (at PT. BPR Surya Yudhakencana in Banjarnegara) - Triana, Wahyu; Rachmawati, Erny; Hariyanto, Eko; Fakhruddin, Iwan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Human resources are one of the resources within a company, namely all the people who carry out activities. The purpose of this research is to analyze the influence of leadership style, organizational culture, and compensation on employee performance through motivation as an intervening variable at PT. The population of this study was employees of PT BPR Surya Yudhakencana Banjarnegara. Sampling in this study used an accidental sampling technique, while the data obtained in this study was processed statistically using Structural Equation Modeling (SEM). The sample obtained was 110 respondents, this research concluded that Organizational Culture and Leadership Style had a positive effect on motivation, while Compensation did not affect Motivation. Organizational culture and leadership style have a positive effect on employee performance, while compensation does not affect employee performance. Motivation has a positive effect on employee performance, organizational culture, and leadership style have a positive effect on performance through motivation as an intervening variable and compensation does not affect employee performance through motivation as an intervening variable. Therefore, researchers suggest adding other variables that can influence employee performance.